Polymixia melanostoma, a new beardfish from the western Pacific (Teleostei, Polymixiiformes, Polymixiidae) - You-Ci Fan; Yo Su; Chien-Hsiang Lin; Chih-Wei Chang; Hsiu-Chin Lin (ZooKeys)
A new species of beardfish, genus Polymixia, is described based on three specimens collected in Taiwanese waters and off the Chesterfield Islands of New Caledonia. It can be distinguished from its congeners by the following characters: dorsal-fin rays IV–V, 35–37; gill rakers on outer face of first gill arch 3+1+6=10; scales row between dorsal-fin origin and lateral line vertically 6–8 (S1) and posteriorly 12–14 (S2); pyloric caeca 40; snout rounded, with its surface rough and gelatinous, its tip evidently protrude anterior margin of premaxilla; ctenii on body scales arranged in a wedge-shape, forming three rows; 4th anal-fin spine long, 1.0%–1.2% eye diameter; longer dorsal-fin, 49.6–53.0% SL; blackish oral-branchial cavity. Our maximum-likelihood tree based on mitochondrial COI sequences revealed that the new species is distinct from six congeneric species. Our findings indicate the presence of at least six Polymixia species in Taiwan, highlighting Taiwan and adjacent areas as a region with the highest diversity of this genus.